“THE UNDERTAKING” AND “THE RELEVANT MARKET”: KEY CONCEPTS IN THE ANALYSIS OF ANTICOMPETITIVE PRACTICES - CRISTINA CUCU (Challenges of the Knowledge Society)
The desire to maintain themselves on a particular market, at a higher level of profitability or at a reasonable level at least, can lead the undertakings to adopt an anticompetitive behaviour more easily. This may result from either the existence of anticompetitive agreements and concerted practices, or the tendency to abuse its dominant position which the undertaking has on a certain market. “The undertaking” and “the relevant market” are the key concepts in the analysis of anticompetitive practices. The active subject of anticompetitive practices is “the undertaking”. This concept has a particular significance in the competition law, different from the common law. Competition rules apply to the conduct of undertakings and associations of undertakings so that the concept of undertaking makes it possible to determine the categories of actors to which the competition rules apply. However, the term undertaking is nowhere defined in the EU Treaties; as such, the concept has generated a complex body of jurisprudence."The market" is a term with pronounced economic resonances; synthetically, the market is the place where supply meets demand. In the context of the competition law, "the market" means "relevant market". The relevant market is the market of product/service in terms of demand and supply, and then superimposed on the geographic market.The analysis of these key concepts necessarily entails the conceptual delimitation of the notions. On this purpose, the relevant legal provisions will be identified in the Romanian and EU law, together with the decisions of the European Court of Justice in this matter.